THE PUBLIC DEBT OF UKRAINE: A NEW DIMENSION OF DYNAMICS AND ARCHITECTURE OF THE MODEL FRAMEWORK OF THE MANAGEMENT SYSTEM - Serhii Petrukha; Nina Petrukha; Roman Miakota (Baltic Journal of Economic Studies)
The article typifies the fiscal directions of public debt management in Ukraine in the conditions of the new economic normality and financial uncertainty caused by the Russian-Ukrainian war and other macroeconomic shocks. The accelerators of these shocks were the Ukrainian peace formula, the policy of adapting the national economic system to wartime conditions, and the triggers of post-war recovery, including those announced by the President of Ukraine, such as humanitarian demining, the reconstruction of energy facilities, and financial inclusion. The study is based on the author's adjustment model for assessing debt dynamics, which is widely used by the IMF, taking into account national specificities. The purpose of the work is to provide a long-term assessment (up to 2029) of fiscal stability, taking into account the invariance of macroeconomic factors and forecasts - GDP growth rates, inflation, exchange rate and debt structure. To this end, two target levels of public debt have been used in the study: 82% of GDP (according to IMF forecasts) and 60% of GDP (according to the Maastricht Treaty). The research methodology is based on the application of two empirical methods to assess debt dynamics: through debt issuance and financing needs. A ten-year statistical series (2015-2024) was used to construct scenarios for the evolution of debt dynamics, taking into account likely macroeconomic shocks. The modelling was grounded in the following variables: primary budget balance, effective interest rate, economic growth rate and exchange rate. Fan charts were employed to illustrate the risks and demonstrate the probability of reaching certain debt levels, depending on the invariance of the level of macroeconomic uncertainty. The findings of the study suggest that in order to attain the targeted public debt level of 82% of GDP, it is imperative to ensure an annual primary budget surplus amounting to 1.38% of GDP during the 2025–2029 period. To achieve a more ambitious goal involving a 60% of GDP target, it is necessary to establish conditions conducive to an annual surplus amounting to 2.43% of GDP. Utilising the aforementioned scenarios and macroeconomic shocks as a foundation, the article demonstrates that in the absence of fiscal correction measures, the public debt will surpass 100% of GDP by 2029. The principal risk factors identified in the study are as follows: low rates of economic growth, a high level of dependence on foreign aid, demographic challenges and high costs for meeting the needs of the security and defence forces. Empirical evidence has demonstrated that the exchange rate and the real interest rate are the predominant factors influencing debt dynamics, thereby exacerbating the debt burden. The conclusions emphasise the necessity to approximate the optimal practices of fiscal consolidation and to implement measures, including those envisaged by the National Revenue Strategy until 2030, in order to increase the revenues of the state budget of Ukraine. In addition, the introduction of a progressive scale of taxation on high incomes is justified and recommended, as are increased tax rates on real estate, rent, and natural resources, as well as increased excise taxes on tobacco, alcohol, and fuel. Furthermore, it emphasises the necessity of a gradual reduction in public expenditures, particularly in the post-war period. The purpose of this article is to provide a systematic overview of the international experience of countries recovering from conflicts. It is argued that in order to ensure the stability of public finances, it is necessary to reduce expenditure on security and defence forces, and on the public sector of the economy. In this context, it is assumed that one of the conditions for the successful implementation of the fiscal correction is the completion of the active phase of the war by the end of 2025 and the consideration of additional caveats regarding the maintenance of a high debt burden in the short, medium and probably the long term perspective due to significant budgetary costs for reconstruction of infrastructure, social protection and economic development. Taking into account the new economic normality and the likely risks (threats), the authors propose to revise the macroeconomic forecasts and to develop additional scenarios for fiscal risk management, including during the preparation of public debt management programmes for 2025-2029.